ASSESSMENT DRIVEN INTEGRATED LEARNING (ADIL): ASSESSMENT DIRECTED MEDICAL EDUCATION (ADME) CURRICULUM - Khan, Junaid Sarfraz (Journal of Ayub Medical College Abbottabad, 2009)
Assessment has been shown to drive learning. For assessment to drive learning in the right direction, it needs to fulfil certain criteria including reliability, validity, educational impact, feasibility, acceptability to stakeholders, cost-effectiveness etc. Assessment has the greatest effect as a driving force in learning if it is authentic, context relevant and samples widely. In this paper, we present a new curriculum design and a model for experiential learning through assessment. We call it Assessment Directed Medical Education (ADME) Curriculum using Assessment Driven Integrated Learning (ADIL). In this model, we propose a cent percent rightest shift in the curriculum design and learning strategy by using assessment as the sole tool to a self-directed learning process through supervised simulated and real-patient encounters testing competencies in cognitive, psychomotor and affective domains in an integrated approach utilising key resources for active learning. It is presumed that, this will, in the long term improve health care delivery by producing competent healthcare professionals that have learned through direct student-'˜patient' encounters from day one of their medical education and are competent in making professional judgments, exhibit appropriate skills and behaviours. Keywords: Assessment, Learning technique, CME, Curriculum, Evaluation, Competency based